2008
DOI: 10.1590/s1516-35982008000200023
|View full text |Cite
|
Sign up to set email alerts
|

Características quantitativas e qualitativas da carcaça de novilhas alimentadas com diferentes fontes energéticas em dietas à base de cascas de algodão e de soja

Abstract: RESUMO -Objetivou-se avaliar as características de carcaça e a composição físico-química e de ácidos graxos do músculo Longissimus de novilhas em confinamento alimentadas com cascas de algodão (CAL) e de soja (CSO) como volumosos e com diferentes fontes energéticas, como milho moído, farelo de gérmen de milho (FGM) ou farelo de arroz integral (FAR). Foram utilizadas 24 novilhas mestiças com peso corporal de abate de 350 ± 35 kg, distribuídas em delineamento inteiramente casualizado, com três tratamentos (dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
2
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 16 publications
(22 reference statements)
2
15
2
8
Order By: Relevance
“…The moisture average (73.3%) were similar to the values observed by Prado et al (2008a) Kazama et al (2008) suggested that variation in moisture percentage occurs when there is variation in total lipids percentage. However, in this study, the total lipids percentage changes only from 1.29 to 1.47% among genetic groups.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The moisture average (73.3%) were similar to the values observed by Prado et al (2008a) Kazama et al (2008) suggested that variation in moisture percentage occurs when there is variation in total lipids percentage. However, in this study, the total lipids percentage changes only from 1.29 to 1.47% among genetic groups.…”
Section: Resultssupporting
confidence: 83%
“…However, there was no difference (P>0.05) between Canchin and Charolais × Caracu genetic groups and Caracu and Aberdeen Angus × Canchin genetic groups. Different values were verified by Kazama et al (2008) and Prado et al (2008a), who observed inferior values of n-3 for genetic group Angus × Canchin of 0.48%.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Much of the acid vacenic absorbed is converted into CLA in the adipose tissue of the animal cattle by the action of the enzyme Δ9 -"desaturase" (Griinari & Bauman, 1999;Bauman, 1999). Kazama et al (2008) raises a hypothesis that CLA produced by ruminal biohydrogenation of linoleic acid is an intermediate transient, while vacenic acid is accumulated in the rumen and it is available for absorption, an assertion based on the speed of the conversion rate of linoleic and α -linolenic acids in trans -vacenic acid that is faster than the transformation of trans -vacenic stearic acid (Izumi et al, 2002.…”
Section: Resultsmentioning
confidence: 99%
“…Para bovinos estes parâmetros são de fundamental importância (Pacheco et al, 2005). Segundo Restle et al (1999), Costa et al (2002) e Kazama et al (2008), em bovinos, o peso e o rendimento da carcaça são medidas de interesse dos frigoríficos para avaliação do produto adquirido e dos custos operacionais, visto que carcaças com pesos diferentes demandam mesma mão-de-obra e mesmo tempo de processamento. Atualmente o peso de carcaça é a forma mais utilizada pelos frigoríficos.…”
Section: Introductionunclassified